PEMANFAATAN SILIKAT BENTONIT TERSUSPENSI NaCl, MgCl2, DAN CaCl2 UNTUK ISOLASI DNA METAGENOMIK DARI TANAH HUTAN MANGROVE - Luh De Dwi Jayanthi; Ida Ayu Gede Widihati; I Nengah Wirajana (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
The aim of this study was to compare the isolated metagenomic DNA of mangrove soil in Suwung Kauh Beach, Bali by utilizing suspended bentonite of NaCl, MgCl2 and CaCl2. The metagenomic DNA isolation was performed by directly lysis method from soil with lysis buffer and heat-shock, and then continued by DNA extraction with suspended bentonite of NaCl, MgCl2 and CaCl2. Preparation of suspended bentonite was done in 1 M NaCl, MgCl2 and CaCl2. The results of metagenomic DNA isolation were analysed by gel agarose electrophoresis and spectrophotometer Nano at wave length 230, 260, and 280 nm. The results of gel agarose electrophoresis showed that DNA was not detected in the first elution from all suspended bentonite, but DNA was only detected in the first supernatant before elution from Na-bentonite and Mg-bentonite suspended. The DNA bands were most thick in the supernatant before the elution of Na-bentonite. This result indicated that Na-bentonite adsorption to metagenomic DNA was lower than the other bentonite suspended. The DNA band was not detected in the first supernatant and the first elution from Ca-bentonite that indicated that DNA adsorption was stronger than the other and was not breakable from this suspended. The results of spectrophotometer nano showed that the metagenomic DNA isolated by suspended bentonite of NaCl, MgCl2 and CaCl2 were contaminated by humic acid and protein.